2021
DOI: 10.1101/2021.12.17.473248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron spike mediated immune escape and tropism shift

Abstract: The Omicron variant emerged in southern Africa in late 2021 and is characterised by multiple spike mutations across all spike domains. Here we show that the Omicron spike confers very significant evasion of vaccine elicited neutralising antibodies that is more pronounced for ChAdOx-1 adenovirus vectored vaccine versus BNT162b2 mRNA vaccine. Indeed neutralisation of Omicron was not detectable for the majority of individuals who had received two doses of ChAdOx-1. Third dose mRNA vaccination rescues neutralisati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
107
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 57 publications
16
107
1
2
Order By: Relevance
“…The reduced severity of Omicron as compared to Delta is consistent with early laboratory evidence that there is a reduction in lower lung infectivity, deficient cell entry, and a reduction in syncytium formation due to reduced ability of the spike protein to mediate plasma membrane fusion. [178], [179] A decrease in severe disease is also consistent with preliminary clinical and epidemiological evidence that had emerged by the time of this manuscript's preparation, suggesting that patients had less severe disease in South Africa. [180] Reduced severe disease in South Africa may be due to a particularly high degree of seroprevalence in South Africa as a result of prior infection and vaccination of the vulnerable population.…”
Section: Predicting Omicron Disease Severitysupporting
confidence: 82%
See 1 more Smart Citation
“…The reduced severity of Omicron as compared to Delta is consistent with early laboratory evidence that there is a reduction in lower lung infectivity, deficient cell entry, and a reduction in syncytium formation due to reduced ability of the spike protein to mediate plasma membrane fusion. [178], [179] A decrease in severe disease is also consistent with preliminary clinical and epidemiological evidence that had emerged by the time of this manuscript's preparation, suggesting that patients had less severe disease in South Africa. [180] Reduced severe disease in South Africa may be due to a particularly high degree of seroprevalence in South Africa as a result of prior infection and vaccination of the vulnerable population.…”
Section: Predicting Omicron Disease Severitysupporting
confidence: 82%
“…However, the model’s predictions are consistent with the preliminary data showing that Omicron may have deficient cell entry and less induction of cell-cell fusion as compared to wild type (ancestral genome) as well as Delta. [178] It has also been suggested based on free energy calculations that the Omicron spike protein has deficient ACE2 binding as compared to wild type or Omicron. [182] Even if these and other preliminary results and predictions of lower severity on an individual basis bear out, epidemiological evidence clearly shows that Omicron is highly transmissible, significantly more so than Delta.…”
Section: Resultsmentioning
confidence: 99%
“…Omicron putatively has a shorter incubation period than prior variants. Symptoms are more intense in the upper respiratory track, and the virus appears to be less pathogenic in the lower airway compared to prior variants (11). One small study with five positive health care workers suggested detection is faster from oral versus nasal swabs (12).…”
Section: Discussionmentioning
confidence: 99%
“…With 37 mutations in its spike, this variant shows striking immune evasion while it also displays increased binding affinity with human ACE2 relative to the WT strain 15,16,28 . Recent reports also showed that the Omicron S exhibits reduced furin cleavage and less S1 shedding 45,46 . It is essential to understand how the mutations present in the Omicron S contribute to the higher transmissibility and immune escape observed for this threatening variant.…”
Section: Discussionmentioning
confidence: 96%